Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Pakan Ternak Probiotik di Desa Mekarlaksana Kecamatan Cikancung Kabupaten Bandung - Ningrumsari, Ida; Herlinawati, Lina (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2016)
Community independent chicken farmers in the village Mekarlaksana, District Cikancung Bandung regency, do not know the chicken feed probiotics therefore the purpose of this service is to empower boiler chicken farmers use chicken feed probiotics. During this time broiler breeders using chicken feed in the market / store. On this occasion we Team Community Agricultural High School (STP) of West Java is appropriate to provide empowerment chicken feed probiotics by: 1). Counseling, 2) training, 3) Guidance and Development, 4) Assisting the procurement of feed ingredients and 5) Discussion and consultation.